Autistic spectrum disorders, personality disorder and offending in a transgender patient: clinical considerations, diagnostic challenges and treatment responses. Issue 3 (4th July 2016) - Baker, Philip; Shweikh, Eman
Abstract : Purpose: – The case of a woman with a history of offending and prolonged imprisonment is given. The purpose of this paper is to explore the complex interplay between diagnoses of autistic spectrum disorder (ASD), personality disorder and gender dysphoria. A discussion on useful and less useful treatment approaches follows, given the unusual and complex clinical presentation. Design/methodology/approach: – This is a case report with a summary of the background to this under-researched area. Findings: – The way in which the diagnostic picture clarified over time is explained. The difficulties in accurately diagnosing are put forward and strategies to address this are suggested. Successful treatment of unusual clinical problems may require highly individualised care within generic services. Originality/value: – The authors know of no similar case reports in the published literature. The clinical associations between ASDs, personality disorders and gender dysphoria, in forensic mental health populations, appears to be unexplored in the literature.